An Economic Model of Friendship: Homophily, Minorities, and Segregation - Currarini, Sergio; Jackson, Matthew O.; Pin, Paolo (Econometrica, 2009)
We develop a model of friendship formation that sheds light on segregation patterns observed in social and economic networks. Individuals have types and see type-dependent benefits from friendships. We examine the properties of a steady-state equilibrium of a matching process of friendship formation. We use the model to understand three empirical patterns of friendship formation: (i) larger groups tend to form more same-type ties and fewer other-type ties than small groups, (ii) larger groups form more ties per capita, and (iii) all groups are biased towards same-type relative to demographics, with the most extreme bias coming from middle-sized groups. We show how these empirical observations can be generated by biases in preferences and biases in meetings. We also illustrate some welfare implications of the model.